INTERDISCIPLINARITY AROUND “CALÇADA PORTUGUESA” SIDEWALK - Melo, Helena (European Scientific Journal, ESJ, 2013)
We find the "Calçada Portuguesa" sidewalk paving an interesting example of the collaboration of various interdisciplinary fields, such as Mathematics, Arts, Architecture, History, Tourism, Technology, Entrepreneurship, and many others. This work will focus on one possible use, the paving of sidewalks, highlighting the interest that arises from each mentioned areas, its concept, and its applications.